Establishing the optimal adenosine 5′-monophosphate level for hybrid striped bass Morone chrysops × Morone saxatilis: Effects on growth performance, nutrient digestibility, and immune modulation during acute and chronic stress - De Cruz, Clement Roy; Yamamoto, Fernando Y.; Castillo, Sergio; Gatlin, Delbert M. (Elsevier, 2020)
Five separate feeding trials were conducted with juvenile hybrid striped bass to evaluate the effects of dietary adenosine 5′-monophosphate (AMP) on growth performance, innate immunity, digestibility, digestive enzyme activity, and physiological responses after acute and chronic stress challenges. For all trials, a basal diet was formulated principally from soybean meal, soy protein concentrate, and fishmeal to contain 40% crude protein, 10% lipid, and 2.5 kcal estimated digestible energy g−1. The experimental diets were prepared for the dose-response trial by supplementing AMP to the basal diet at six graded levels (0, 0.25, 0.5, 0.75, 1.5 and 2.0% of dry weight) at the expense of cellulose. Based on weight gain and protein retention responses after 8 weeks of feeding, the minimum requirement was estimated in a two-slope broken line model to be 0.46% and 0.34% of dry diet, respectively. Therefore, a diet supplemented with 0.5% AMP was evaluated against the basal dietary treatment in the four follow-up trials. The subsequent digestibility trial (4-week) showed that dietary AMP at 0.5% significantly (P < 0.05) improved apparent digestibility coefficient for organic matter and energy. Nevertheless, after 8 weeks of feeding, there were no significant interaction effects on the digestive enzymes trypsin, lipase, amylase, alkaline and acid phosphatases due to diet (basal and 0.5% AMP), intestinal section (anterior and posterior), or sampling time (10 h after and 20 h post prandial). In the acute-stress challenge trial, fish fed the diet with 0.5% AMP for 6 weeks had significant (P < 0.05) enhancement of innate immunity as reflected in the activity of plasma anti-protease at 0.5 and 1 h post-stress challenge (air exposure). A subsequent chronic stress trial, in which fish were cultured in 15 ppt salinity for 4 weeks, showed that plasma lysozyme activity and anti-protease activity were significantly immunosuppressed in fish fed the basal diet compared to those fed the diet supplemented with AMP at 0.5%. In addition, blood glucose was significantly higher in fish fed the basal diet; whereas, no statistical significance was detected in weight gain, plasma cortisol, hematocrit, or osmolality between both dietary treatments. To conclude, this study demonstrated that an exogenous supply of AMP at 0.5% of diet enhanced growth response of juvenile hybrid striped bass, enhanced their protein retention and increased digestibility coefficients for organic matter and energy. Furthermore, dietary AMP at 0.5% of dry weight showed capabilities to modulate immune responses under stressful conditions through enhancement of innate immunity and resistance to stress-induced immunosuppression.